The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/bs.mie.2017.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Deuterium Isotope Effects in Cytochrome P450 Reactions

Abstract: Cytochrome P450 (P450, CYP) research provides many opportunities for the application of kinetic isotope effect (KIE) strategies. P450s collectively catalyze oxidations of more substrates than any other group of enzymes, and C-H bond cleavage is a major feature in a large fraction of these reactions. The presence of a significant primary deuterium KIE is evidence that hydrogen abstraction is at least partially rate-limiting in the reactions, and this appears to be the case in many P450 reactions. The first repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 76 publications
1
42
1
Order By: Relevance
“…Thisi si nl ine with previous studies in which substantially larger KIEs were observed for aliphatic than for aromatic hydroxylation by P450s. [30] The increasein4'-OH-MF formationa fter deuteration may be well explained by metabolic switching resulting from the strongly decreased 3'-hydroxylation. Thus, our kinetic isotope effect measurements for these reactionss uggestt hat rapid interconversion between catalytically active poses for 3'-OH-MF and 4'-OH-MF formation is possible and accordingly,that k i and k Ài values for binding-poseinterchange and/or k b and k u values are probably highert han k p for the corresponding product formations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thisi si nl ine with previous studies in which substantially larger KIEs were observed for aliphatic than for aromatic hydroxylation by P450s. [30] The increasein4'-OH-MF formationa fter deuteration may be well explained by metabolic switching resulting from the strongly decreased 3'-hydroxylation. Thus, our kinetic isotope effect measurements for these reactionss uggestt hat rapid interconversion between catalytically active poses for 3'-OH-MF and 4'-OH-MF formation is possible and accordingly,that k i and k Ài values for binding-poseinterchange and/or k b and k u values are probably highert han k p for the corresponding product formations.…”
Section: Resultsmentioning
confidence: 99%
“…13 ]mefenamic acid, so that eventual effects of these side products on the reactions were applicable to both labelled and unlabeled mefenamic acid to the same extent. [30] All incubations were performed with 100 nm P450 in 100 mm potassium phosphate buffer (pH 7.4) supplemented with 5mm MgCl 2 and 2mm EDTA. To tal substrate concentrations of the mixture of labelled and unlabeled mefenamic acid were 75 and 750 mm.R eaction mixtures (total volume 100 mL) were pre-warmed at the incubation temperature for 10 min, before initiating the reaction by addition of aN ADPH regenerating system (final concentrations of 0.5 mm NADPH, 10 mm glucose 6-phosphate, and 0.4 unit mL À1 glucose-6-phosphate dehydrogenase).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second direction refers to the use of deuterium depleted water as an adjuvant in the treatment of cancer [19,20]. The result of the change in D/H ratio is manifested in the form of kinetic isotopic effect [21][22][23][24], which is characterized by a change in the rate of absorption, distribution, biotransformation, and excretion of the medicines. Development of methodological approaches to drugs quality control based on water O) mutarotation of carbohydrates had the different kinetic mechanisms.…”
Section: Introductionmentioning
confidence: 99%